An Up-down Determination of the Required Seated Duration After Intrathecal Injection of Bupivacaine and Fentanyl for the Prevention of Hypotension During Cesarean Delivery. Issue 3 (September 2018) - Moore, A.; El-Mouallem, E.; El-Bahrawy, A.; Kaufman, I.; Moustafa, M.; Derzi, S.; Hatzakorzian, R.; Lipishan, W.
Abstract : ( Can J Anaesth 2017;64:1002–1008) Prolonged seated time following intrathecal injection can prevent hypotension during cesarean delivery by limiting the upward spread of hyperbaric local anesthesia, but the limited studies of this technique have shown conflicting results. This study aimed to determine the median seated time for the prevention of hypotension following intrathecal injection of either 11.25 or 15 mg of hyperbaric bupivacaine with preservative-free morphine and fentanyl. The secondary aim of the study was to measure the rates of supplemental analgesia requirements for patients with who remained seated for an extended duration after spinal anesthesia administration.